Relative importance of inflammatory markers (erythrocyte sedimentation rate, C-reactive protein, procalcitonin, and interleukins-6) in neonatal sepsis - Satyaki Das; Jaydeb Ray (Wolters Kluwer Medknow Publications, 2016)
Objective: Early diagnosis and treatment decreases the mortality and morbidity of neonatal sepsis(NS). The aim of this study was to find out the level of different inflammatory markers in neonatal sepsis. Methods: Forty two term neonates with non-sepsis (n = 17), clinical (n = 10) and proven (n = 15) sepsis were evaluated. Blood cultures were obtained and ESR, CRP, procalcitonin, IL-6 levels were measured. Statistical analysis was performed to look for association between NS and different inflammatory markers and to compare the strength of association among the markers. Findings: Among the 42 neonates, CRP level was found to be elevated in 27 neonates, ESR in 22 neonates, both procalcitonoin and IL-6 in 24 neonates respectively. Both sensitivity and specificity of procalcitonin and IL-6 were high compare to CRP. Conclusions: Blood culture significantly increases the proven sepsis status among neonates with suspected sepsis. ESR is a poor predictor of NS. Newer inflammatory markers namely procalcitonin and IL-6 were found to have greater value than CRP, but not ESR.